Control and surveillance on the Internet: computational technique as a mechanism for power increase - Rodrigues, Gustavo Alarcon [UNESP]; Marchetto, Patrícia Borba [UNESP] (Centro Universitario La Salle - UNILASALLE, 2021)
This paper aims to analyze the manifestation of control and surveillance mechanisms used by the state and corporate spheres, comprehending how it is forced over people through the internet and its satellite technologies. Due to the disruptive progress of contemporary society, it is possible to foresee a clear change in social dynamics including the expression of power, reflecting in a series of new models within the programmed, open and almost infinite environment of internet. Therefore, this research starts with a critical analysis of said control and surveillance techniques, especially the computational and informational ones, advancing to understand its expression as a tool of domination. It is important to understand technique differences while acting on “the world of atoms and on the world of bits”, guiding it to comprehend new theorized models about the exercise of control and surveillance in the programmed environment. The proposed paper has the inductive method as its methodological paradigm, taking models theorized by selected academics as basis for understanding the control models in the social environment. It is important to note that there is the collection of a bibliographic review of works, articles and news related to the topic as support for the chosen methodology.
Controle e vigilância na Internet: técnica computacional como mecanismo de engendramento de poder
Keywords: Algocracy; Control; Domination; Internet; Surveillance